Premium IOLs in Glaucoma - Ichhpujani, Parul (J Curr Glaucoma Pract, 2013)
Advanced technology or premium intraocular lenses have been developed to meet the patient expectations of perfect distance and near vision without the need for spectacles. Careful patient selection is critical when implanting these implants. This brief review focusses mainly on multifocal and toric IOLs and their application and limitations in patients with glaucoma. How to cite this article: Ichhpujani P, Bhartiya S, Sharma A. Premium IOLs in Glaucoma. J Current Glau Prac 2013;7(2): 54-57.